2014
DOI: 10.1190/geo2013-0095.1
|View full text |Cite
|
Sign up to set email alerts
|

Seismic reflector imaging using internal multiples with Marchenko-type equations

Abstract: We present an imaging method that creates a map of reflection coefficients in correct one-way time with no contamination from internal multiples using purely a filtering approach. The filter is computed from the measured reflection response and does not require a background model. We demonstrate that the filter is a focusing wavefield that focuses inside a layered medium and removes all internal multiples between the surface and the focus depth. The reflection response and the focusing wavefield can then be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
207
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 194 publications
(210 citation statements)
references
References 20 publications
3
207
0
Order By: Relevance
“…It has been shown that all events in the Green's functions can be retrieved with correct amplitudes for K → ∞, given that the initial focusing function obeys eq. (24) Slob et al 2014;Wapenaar et al 2014a). In practice, only a few iterations are generally sufficient to predict the dominant internal multiples in the wavefield with fairly accurate amplitudes, as we will demonstrate in the synthetic examples that follow.…”
Section: Green's Function Retrievalmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that all events in the Green's functions can be retrieved with correct amplitudes for K → ∞, given that the initial focusing function obeys eq. (24) Slob et al 2014;Wapenaar et al 2014a). In practice, only a few iterations are generally sufficient to predict the dominant internal multiples in the wavefield with fairly accurate amplitudes, as we will demonstrate in the synthetic examples that follow.…”
Section: Green's Function Retrievalmentioning
confidence: 99%
“…also been mentioned by Sheiman (private communication, 2014). During higher-order iterations, the amplitudes of the events are updated, as illustrated by Wapenaar et al (2014a), Broggini et al (2014b) and Slob et al (2014).…”
Section: Step 2: Updating the Downgoing Wavefieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here the window function cuts off precisely one event at τ d (p), the arrival time of the direct wave of the scalar Green's function [24]. We generalize this for the elastodynamic situation.…”
Section: Single-sided Marchenko Focusing: Theorymentioning
confidence: 99%
“…Marchenko imaging (Broggini and Snieder, 2012;Slob et al, 2014;Wapenaar et al, 2014) is a novel seismic imaging technique that has the potential to produce seismic reflection images, free of artifacts related to internal multiples van der Neut et al, 2015;Ravasi et al, 2016) and surface-related multiples (Singh et al, 2017). An intriguing question is whether the multiples are only eliminated or whether they also contribute to the imaged reflectors.…”
Section: Introductionmentioning
confidence: 99%